The relationship between race and emergency medical services resuscitation intensity for those in refractory-arrest - Justin Yap; Jacob Hutton; Marina Del Rios; Frank Scheuermeyer; Malini Nair; Laiba Khan; Emad Awad; Takahisa Kawano; Valerie Mok; Jim Christenson; Brian Grunau (Resuscitation Plus)
Background: Previous studies have reported race-based health disparities in North America. It is unknown if emergency medical service (EMS) treatment of out-of-hospital cardiac arrest (OHCA) varies based on race. We sought to compare markers of resuscitation intensity among different racial groups. Methods: Using data of adult EMS-treated OHCAs from the Trial of Continuous or Interrupted Chest Compressions During CPR, we analyzed data from participants for whom on-scene return of spontaneous circulation (ROSC) was not achieved. We fit multivariate regression models using a generalized estimating equation, to estimate the association between patient race (White vs. Black vs. “Other”) and the following markers for resuscitation intensity: (1) resuscitation attempt duration; (2) intra-arrest transport; (3) number of epinephrine doses; (4) EMS arrival-to-CPR interval, and (5) 9–1–1 to first shock. Results: From our study cohort of 5370 cases, the median age was 65 years old (IQR: 53–78), 2077 (39 %) were women, 2121 (39 %) were Black, 596 (11 %) were “Other race”, 2653 (49 %) were White, and 4715 (88 %) occurred in a private location. With reference to White race, Black race was associated with a longer resuscitation attempt duration and a lower number of epinephrine doses; Black and “Other” race were both associated with a lower odds of intra-arrest transport. Conclusion: We identified race-based differences in EMS resuscitation intensity for OHCA within a North American cohort, although 40% of race data was missing from this dataset. Future research investigating race-based differences in OHCA management may be warranted.